2020
DOI: 10.1097/prs.0000000000006378
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Outcomes of Intraarticular Fat Transplantation for Thumb Carpometacarpal Joint Osteoarthritis: Case Review of 99 Joints

Abstract: Background: This study aims to present a new therapeutic option for the treatment of thumb carpometacarpal joint osteoarthritis. Knowing that autologous fat may be beneficial for osteoarthritis through antiinflammatory and chondroprotective effects, the authors transplanted autologous adipose fat into the thumb carpometacarpal joint with the objective of postponing definite resection arthroplasty surgery. Methods: In this pilot study, the authors perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 31 publications
3
30
0
4
Order By: Relevance
“…Recent human studies have demonstrated satisfactory results with the intra-articular administration of purified and micro-fragmented adipose tissue for the treatment of knee, 18,19 subtalar, 20 carpometacarpal 21,22 and thumb osteoarthritis. [23][24][25] In veterinary literature, a recent study 26 suggested clinical evidence of pain control over a period of up to 180 days with intra-articular administration of autologous purified and micro-fragmented adipose tissue for the treatment of osteoarthritis in dogs. Several authors evaluated the effects of simultaneous intra-articular injection of culture-expanded autologous adipose-derived stem cells and platelet-rich plasma, [27][28][29][30][31] or plasma rich in growth factors 28,29 in dogs with stifle osteoarthritis 27 and hip osteoarthritis 28-32 using a plate force 29,30,32 or Tekscan pressuresensitive walkway analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent human studies have demonstrated satisfactory results with the intra-articular administration of purified and micro-fragmented adipose tissue for the treatment of knee, 18,19 subtalar, 20 carpometacarpal 21,22 and thumb osteoarthritis. [23][24][25] In veterinary literature, a recent study 26 suggested clinical evidence of pain control over a period of up to 180 days with intra-articular administration of autologous purified and micro-fragmented adipose tissue for the treatment of osteoarthritis in dogs. Several authors evaluated the effects of simultaneous intra-articular injection of culture-expanded autologous adipose-derived stem cells and platelet-rich plasma, [27][28][29][30][31] or plasma rich in growth factors 28,29 in dogs with stifle osteoarthritis 27 and hip osteoarthritis 28-32 using a plate force 29,30,32 or Tekscan pressuresensitive walkway analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The following complications were described by Haas et al . 13 : one haematoma after liposuction occurred out of 89 patients (99 CMC joints). One patient suffered from severe pain and subsequently received firstly intravenous analgesics, later, after discharge, the pain was treated with oral medication and stopped 3 weeks postoperatively.…”
Section: Resultsmentioning
confidence: 98%
“…The wider cohort of patients available so far was published by Haas et al . 13 , who performed fat grafting in 99 first CMC joints. They found that pain under stress at 2 and 6 weeks as well as 3, 6 and 12 months was significantly lower than at baseline (p<0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on a wider cohort of TBOA patients (n 99) treated with autologous fat injection was derived from the most recent study by Haas et al (Haas et al, 2020). They reported that pain during activities at 2 and 6 weeks as well as 3, 6, and 12 months was significantly lower than at baseline.…”
Section: New Emerging Intra-articular Therapiesmentioning
confidence: 99%